Penentuan Jenis Mineral Liat Alofan Tanah Andisol di Desa Dolat Rakyat Kecamatan Tiga Panah Kabupaten Karo - Jupri Simamora; Purba Marpaung; Alida Lubis (Universitas Sumatera Utara, 2015)
The aim of the research was to determinate type of Allophane minerals by means of Thermogram and to know type of Allophane minerals with Allophane–Organic Matter relations. The research was done in Dolat Rakyat villages, District of Tiga Panah Karo Regency, In Soil Fertility Laboratory University of North Sumatera, and College of Chemical Industry (PTKI), Medan in June - October 2014. Soil type is Andisol. The result of the research in Dolat Rakyat Village Tiga Panah District, Regency of Karo Thermogram interpretation showed that type of Allophane minerals Andisol that is Allophane B. Allophane-Organic Matter relations showed that type of Allophane minerals is Allophane B with positive relations between Allophane-Humic Acid; negative relations between Allophane-Fulvic Acid, and Allophane-Humic Acid+Fulvic Acid.Key Word : Allophane, Andisol, Organic Matter